Clinical efficacy and tendon integrity of patients with subscapularis tear by the technique of arthroscopic single external row repair - Zheng, Weipeng; Weng, Rui; Wu, Xiaohang; Liu, Zhijun; Liao, Zhihao; Chen, Sheng; Zheng, Suming; Yi, Zhiyong; Huang, Xudong; Wei, Hewei (Frontiers in Medicine, 2023)
Background With the development of arthroscopic technology and equipment, arthroscopy can effectively repair the tear of the subscapular muscle. However, it is difficult to expose the subscapular muscle and operate it under a microscope. In this study, the SwiveLock® C external row anchor under arthroscopy was applied to repair the tear of the subscapular muscle in a single row, which is relatively easy to operate with reliable suture and fixation, and its efficacy was evaluated. Purpose This study aimed to assess the clinical efficacy and the tendon integrity of patients who had subscapularis tears by adopting the single-row repair technique with a SwiveLock® C external row anchor. Methods Patients who had the subscapular muscle tear either with or without retraction were included, and their follow-up time was at least 1 year. The degree of tendon injury was examined by magnetic resonance imaging (MRI) and confirmed by arthroscopy. The tendon was repaired in an arthroscopic manner by utilizing the single-row technique at the medial margin of the lesser tuberosity. One double-loaded suture SwiveLock® C anchor was applied to achieve a strong fixation between the footprint and tendon. The range of motion, pain visual simulation score, American Shoulder and Elbow Surgeons (ASES) score, and Constant score of shoulder joint were evaluated for each patient before the operation, 3 months after the operation, and at least 1 year after the operation. Results In total, 110 patients, including 31 males and 79 females, with an average age of 68.28 ± 8.73 years were included. Arthroscopic repair of the subscapular tendon with SwiveLock® C external anchor can effectively improve the range of motion of the shoulder joint. At the last follow-up, the forward flexion of the shoulder joint increased from 88.97 ± 26.33° to 138.38 ± 26.48° (P < 0.05), the abduction range increased from 88.86 ± 25.27° to 137.78 ± 25.64° (P < 0.05), the external rotation range increased from 46.37 ± 14.48° to 66.49 ± 14.15° (P < 0.05), and the internal rotation range increased from 40.03 ± 9.01° to 57.55 ± 7.43° (P < 0.05). The clinical effect is obvious. The constant shoulder joint score increased from 40.14 ± 15.07 to 81.75 ± 11.00 (P < 0.05), the ASES score increased from 37.88 ± 13.24 to 82.01 ± 9.65 (P < 0.05), and the visual analog scale score decreased from 5.05 ± 2.11 to 1.01 ± 0.85 (P < 0.05). In the 6th month after the operation, two cases (1.81%) were confirmed to have re-tears via MRI. Conclusion In this study, we repaired the subscapularis muscle with a single-row technique fixed by SwiveLock® C anchor and FiberWire® sutures and evaluated its efficacy. The results showed that the clinical effect of single-row arthroscopic repair was satisfactory and that reliable tendon healing could be achieved.